Gender coloniality and its influence on the perception of black masculinity: a conflict in Gertrudis Gómez de Avellaneda’s antislavery message in Sab - Santoni Morro, Isis A. (2023)
This article examines gender coloniality and its influence on the perception of black masculinity in Gertrudis Gómez de Avellaneda’s Sab. In the novel, the Afro-descendant man is perceived as a threat to the colonial order and white femininity, which betrays the «black fear». Important themes are presented in a superficial tone, as the protagonist’s goal is not to abolish slavery, but to free himself in order to love Carlota. From this it is identified that the novel’s anti-slavery message is ineffective, as Sab is a spokesperson for the white feminist struggle and is denied her own liberation by presenting the antislavery struggle as an inferior concern to women’s liberation.